Relay seeding of berseem in mustard crop influences system productivity and economics - Singh, Y P (Indian Farming, 2023)
In the semi-arid tropics, mustard-based cropping systems grown in monocropping resulted in declined soil fertility, system productivity and profitability. It was observed that by growing the relay crop of berseem in mustard, soil fertility, system productivity and profitability can be improved. The relay cropping of berseem in mustard was introduced in 2018–19 in 32 ha in Farmer First Programme (FFP) project adopted villages of Morena district of Madhya Pradesh and its adoption has expanded to 11,800 ha. Compared with existing system of without relay cropping, the relay legume crop of berseem enhanced the productivity of rainy (kharif) season crops- pearl millet, paddy and greengram and winter (rabi) season mustard. Like-wise system-based mustard equivalent yield (MEY) in relay cropping system increased from 35–62% with additional net profit from `29,000-46,300/ha as compared to without relay cropping. The water productivity was also increased from 6–19% with relay cropping as compared to without relay system. Thus, the relay cropping of berseem in mustard gained popularity among farmers as an appropriate farm adequate, knowledge-intensive, eco-friendly, profitable and socially acceptable technology.